(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2025)
While the Homeric epics primarily focus on the Greek and Trojan heroes battling outside Troy’s walls, they also hark back to earlier heroic eras. Among past heroes, Herakles is the most frequently mentioned. The Iliad often references Herakles’ exploits, but the Odyssey only briefly evokes him in a few verses. The most extended mention occurs in the nekyia (Od. 11. 601-627), a passage presenting oddities that have been widely debated and interpreted. This paper considers the passage focusing on the diffuse confusion of temporal levels that it presents in the light of frameworks related to mind and consciousness. Inspired by the seminal works of Snell and Dodds and the controversial yet increasingly validated theories of Jaynes, supported by neuroscientific insights and Damasio’s endorsement, it explores recent research on consciousness in perceiving and describing time. It investigates whether this Homeric passage may reflect a transitional phase from one stage of development of the human cognitive system to a subsequent one characterised by different functional traits.